Combined vesicouterine rupture during second-trimester medical abortion for fetal abnormality after prior cesarean delivery: A case report - Giuseppe Caruso; Vanessa Paladini; Valentina D'ambrosio; Antonella Giancotti; Maria Grazia Piccioni; Innocenza Palaia; Violante Di Donato; Giorgia Perniola; Roberto Brunelli; Francesco Pecorini; Ludovico Muzii; Maria Scudo (Elsevier, 2021)
Introduction: The use of mifepristone and misoprostol for the induction of a second-trimester abortion is common and effective. However, its safety in women with previous cesarean delivery is still controversial, given the potentially higher risk of uterine rupture. Case presentation: We present the case of a 30-year-old woman (G2P1) who experienced vesicouterine rupture with escape of the dead fetus into the bladder during second-trimester induced abortion after prior cesarean delivery. She was successfully managed with conservative surgery. Conclusion: This case highlights the challenges of early diagnosis of vesicouterine rupture during second-trimester medical abortion. We argue that a close monitoring of patients with prior cesarean section is mandatory, particularly if uterine contractions suddenly stop or the fetal head fails to descend. A prompt conservative surgical approach allows preservation of fertility.